The cloacal complex in Pseudocordylus melanotus and in Cordylus cordylus (Sauria: Cordylidae) - Mackay, Henry Calvin (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1993.